Niger : 2016 Article IV Consultation and Request for a Three-Year Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Niger. (IMF Staff Country Reports; Country Report ;, 2017)
This 2016 Article IV Consultation highlights Niger's macroeconomic outcomes, which continue to be affected by security and humanitarian shocks, weak commodity prices, and reduced trade flows to neighboring countries. For 2016, growth is projected at 4.6 percent, slightly higher than the 3.5 percent recorded in 2015, but still only just above the rate of population growth. The medium-term economic outlook is favorable, but remains subject to substantial external and domestic risks. Growth is projected to increase to 5.2 percent in 2017 and to average 6.0 percent during 2018-21, mainly as a result of the expansion of the extractive industries sector and an increase in public and private investments.